Acute cardiopulmonary toxicity of inhaled aldehydes: role of TRPA1. Issue 1 (6th May 2016) - Conklin, Daniel J.
Abstract : Inhalation of high‐level volatile aldehydes, as present in smoke from wildfires and in tobacco smoke, is associated with both acute and chronic cardiopulmonary morbidity and mortality, but the underlying mechanisms are unclear. The transient receptor potential ankyrin 1 (TRPA1) protein forms a cation channel (irritant receptor) that mediates tobacco smoke–induced airway and lung injury, yet the role of TRPA1 in the cardiovascular toxicity of aldehyde exposure is unclear. Physiologically, airway‐located TRPA1 activation triggers an irritant response (e.g., coughing and "respiratory braking") that alters the rate and depth of breathing to reduce exposure. Acrolein (2‐propenal), a volatile, unsaturated aldehyde, activates TRPA1. Acrolein was used as a chemical weapon in World War I and is present at high levels in wildfires and tobacco smoke. Acrolein is thought to contribute to pulmonary and cardiovascular injury caused by tobacco smoke exposure, although the role of TRPA1 in cardiovascular toxicity is unclear. This minireview addresses this gap in our knowledge by exploring literature and recent data indicating a connection between TRPA1 and cardiovascular as well as pulmonary injury due to inhaled aldehydes.